Front Cover. Issue 7 (16th June 2016) - Unknown
Abstract : The cover image, by Manuel J. Steinbauer et al., is based on the Special Issue Article Biogeographic ranges do not support niche theory in radiating Canary Island plant clades, DOI: 10.1111/geb.12425 . Photo Credit: Andreas Schweiger.